Morphological characters variation of Indonesian accession Echinacea purpurea in response to gamma-ray irradiation - Agustina Putri Cahyaningsih; ‪Nita Etikawati‬; Ahmad Yunus (Society for Indonesian Biodiversity, 2022)
Abstract. Cahyaningsih AP, Etikawati N, Yunus A. 2022. Morphological characters variation of Indonesian accession Echinacea purpurea in response to gamma-ray irradiation. Biodiversitas 23: 5351-5359. Indonesia was one of the countries that introduced E. purpurea as a medicinal plant. Accessions of E. purpurea that have been successfully cultivated in Indonesia have narrow genetic diversity, lack accession variation, and have almost uniform tillers. This study was conducted to determine the effect of different doses of gamma-ray irradiation on morphological characteristics of E. purpurea accession B2P2TOOT. The experimental design was a Randomized Block Design with three replications, and six doses of gamma-ray irradiation (0, 15 Gy, 20 Gy, 25 Gy, 40 Gy, and 60 Gy) were used. The qualitative morphological data were presented descriptively; quantitative data were analyzed using ANOVA followed by a DMRT test at a 5% level with SPSS 16.0 application. The Dice similarity algorithm analyzed the similarity index, group analysis, and dendrogram construction using the UPGMA method with the NTSYS 2.02 application. Gamma-ray irradiation treatment increased the survival rate of E. purpurea plants grown in tropical lowlands. A dose of 15-60 Gy gamma irradiation did not affect the qualitative morphology of E. purpurea roots, stems, and leaves. Irradiation at doses of 40 Gy and 60 Gy resulted in flowers with more variation in color, overall flower shape, and arrangement of ray floret. Gamma irradiation significantly affected plant height, leaf length, leaf area, flower angle, and the first day of flowering. The 40 and 60 Gy doses resulted in longer leaves with wider leaf surfaces. The dendrogram revealed that E. purpurea irradiation resulted in two main groups, with doses of 40 and 60 Gy forming their groups and increasing morphological variation by 30% compared to controls.